Directory of World Cinema. - Bell, Emma (Directory of World Cinema Series., 2012)
Bringing to mind rockers and royals, Buckingham Palace and the Scottish Highlands, Britain holds a special interest for international audiences who have flocked in recent years to quality British exports like Fish Tank, Trainspotting and The King?s Speech.